Comparative studies on the repair of achilles tendon ruptures in dogs by carbon fibre and supramid suture - Celal İzci (Eurasian Journal of Veterinary Sciences)
This study was carried out on 40 legs of 20 dogs of varied breed, sex and age. The experimental animals were divided into two groups containing 10 dogs each. In the first group, the tendon ends were sutured with carbon fibre and supramid after the tenotomy. In the second group, following the tenectomy, at first the tendon ends were fixed against each other by using 4/0 stainless steel wire later carbon fibre and supramid were placed like a bridge between the two ends by means of Dexon. In both groups the legs were bandaged covering up the whole hock in an extention state. The bandages were taken off after 17 days of the experiment where tenorrhaphy was applied. However, this was done at 21 st day of the operation where the implantation was tried. Atrophy has formed in soft tissues especially under the hock in cases where the plastared bandage was applied. No complication was observed as to the PVC bandage utilization. The animals for which tenorrhaphy was implemented were allowed for complete free movement at 30 th day, but the other animals for which the implantation was used did so after 35 days. After the recovering period samples had been obtained from the operational region and popliteal lymph nodes under general anesthesia for examining histo-patologically, the animals were euthanatized. As a result, it could be forseen that supramid may be used as a sutured material for the treatment of tendon ruptures in dogs, whereas carbon fibre can be used as an implant material for the same purpose.